The Improvement of English Vocabulary Ability Using Jumbled Words Media - Yuyun Bahtiar (JoEMS (Journal of Education and Management Studies), 2020)
Improvement of English Vocabulary Ability Using Jumbled Words Media Yuyun Bahtiar KH A Wahab Hasbullah University yuyunbahtiar@unwaha.ac.id ©2018 –JoEMS Universitas KH. A. Wahab Hasbullah Jombang ini adalah artikel dengan akses terbuka dibawah lisensi CC BY-NC-4.0 (https://creativecommons.org/licenses/by-nc/4.0/ ). ABSTRACT: The problems of this study are: 1) How is the application of learning using Jumbled Words media in improving vocabulary skills, 2) What is the level of students' vocabulary abilities after using Jumbled Words media The objectives of this study are: 1) To find out the application of learning using Jumbled Words media in improving students 'vocabulary skills, 2) To describe the level of students' vocabulary abilities after learning through using Jumbled Words media This class action research in its implementation uses two cycles, each cycle consisting of planning, action implementation, observation, and reflection. In data collection techniques used are the method of observation, observation sheets in groups, tests and documentation. Whereas in analyzing data in this study is qualitative data analysis. From the above analysis it can be concluded that the use of Jumbled Words media in English subjects at SD Negeri II Widang Tuban is very good when applied to class I students and through jumbled letters media can improve the English vocabulary ability of students of grade I at SD Negeri II Widang Tuban. This is indicated by the fact that in cycle I the average grade was quite good with a score of 66.36 and the percentage of graduation reached 48.48%, the magnitude of this percentage was already said to be good but a review needed to be held, in order to obtain maximum data, we know the standard of learning achievement as explained earlier is 85%. In cycle II the average value of students increased to 80 or can be categorized well, as well as the percentage of learning achievement reached 96.96% and the figure is included in the excellent category. Keywords: Ability; English Vocabulary; Jumbled Words Media. ABSTRAK: Permasalahan penelitian ini adalah:1) Bagaimana penerapan pembelajaran dengan menggunakan media Jumbled Words dalam meningkatkan kemampuan kosakata, 2) Bagaimana tingkat kemampuan kosa kata siswa setelah menggunakan media Jumbled Words Tujuan dari penelitian ini adalah: 1). Untuk mengetahui penerapan pembelajaran dengan menggunakan media Jumbled Words dalam meningkatkan kemampuan kosakata siswa, 2) Untuk mendiskripsikan tingkat kemampuan kosakata siswa setelah melalui pembelajaran dengan menggunakan media Jumbled Words Penelitian tindakan kelas ini dalam pelaksanaannya menggunakan dua siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan, dan refleksi. Dalam teknik pengumpulan data yang digunakan yaitu metode observasi, lembar pengamatan dalam kelompok, tes dan dokumentasi. Sedangkan dalam menganalisis data dalam penelitian ini adalah analisis data secara kualitatif. Dari analisis diatas dapat disimpulkan bahwa penggunaan media Jumbled Words pada mata pelajaran Bahasa Inggris di SD Negeri II Widang Tuban sangat baik bila diterapkan pada siswa kelas I dan melalui media jumbled letters dapat meningkatkan kemampuan kosa kata Bahasa Inggris siswa kelas I SD Negeri II Widang Tuban. Hal ini ditunjukkan dengan diketahui bahwa pada siklus I rata-rata kelas cukup baik dengan angka 66,36 dan prosentase kelulusannya mencapai 48,48%, besarnya prosentase ini sudah dikatakan baik tetapi perlu diadakan review ulang, agar memperoleh data yang maksimal, kita ketahui standar prestasi belajar seperti yang dijelaskan sebelumnya adalah mencapai 85%. Pada siklus II nilai rata-rata siswa meningkat menjadi 80 atau dapat dikategorikan baik, begitu juga dengan prosentase prestasi belajar mencapai 96,96% dan angka tersebut termasuk kategori sangat baik. Kata Kunci: Kemampuan; Vocabulary Bahasa Inggris; Media Jumbled Words. INTRODUCTION In this study, researchers focused on aspects of vocabulary mastery. Vocabulary is defined as a set of all the words understood by the person or all the words that the person is likely to use to construct new sentences. Vocabulary is an important component in language learning. Vocabulary is the most important ingredient and needs to be understood and understood in order to be used properly and correctly. The teacher can create an adequate learning environment or environment so students can find real experiences and be directly involved with tools and media. According to Trianto, (2007), the role of the teacher is very important to create a learning situation. Meanwhile, according to Atik Sustiwi, (2008), in an effort to influence the development of children to actualize all the potential possessed in order to function optimally against several factors that must be considered in order to achieve the expected results. Elanneri Karani, (2011) argues that there are three main functions of the media or teaching aids namely capturing the attractiveness of children's English learning, clarifying concepts, and reinforcing explanations especially about abstract concepts. So that students more easily understand learning with the help of these learning media. By using the concept of Jumbled Words, the researcher will carry out the CAR in SD Negeri II Widang Tuban. The author's strong reason for choosing this school is because this school is an accredited school B. The strength of this school is supported by adequate facilities and infrastructure to support the teaching and learning process. In an effort to improve students' abilities in learning English vocabulary, an effective, interesting and enjoyable medium for students is needed. To overcome this, by using Jumbled Words learning media, it is expected that with Jumbled Words media, these students can be more skilled in increasing vocabulary so that the problem of low student learning outcomes can be overcome. RESEARCH METHODS Research Type This research is a classroom action research. The types of actions studied are as follows: 1). Application of Jumbled Words Media to vocabulary material. 2). The activeness of students during the learning process. According to Suharsimi Arikunto, (2009), this study uses an action research model from Kemmis and Taggart, which is spiral from one cycle to the next. Each cycle includes planning, action, observation, and reflection. The next step in the cycle is a revised planning, action, observation, and reflection. Before entering the first cycle, a preliminary action is taken in the form of identifying the problem The spiral cycle of the stages of classroom action research can be seen in the following figure: Research is planned by implementing class action research which includes components: Planning Arranging the action plan, in this stage the researcher explains about what, why, when, where, by whom, and how the action will be carried out. The ideal action research is actually done in pairs between the party doing the action and the party watching the process. Implementation Action Implementation, this stage is the implementation or application of the contents of the design, which is wearing action in class. Observations Namely observational activities carried out by observers. In this stage, the implementing teacher records little by little what happens in order to obtain accurate data for improvement of the next cycle. Reflection Is an activity to restate what has been done. In this stage the teacher tries to find things that are already satisfying because they are in accordance with the design and carefully recognize things that still need to be fixed. Research Settings and Research Subjects The research settings include: Research location, research time, and The Classroom Action Research cycle as follows: Place of Research The Classroom Action Research was conducted at the Second Elementary School in Widang Tuban for first grade English subjects. Research time This research was conducted on Monday 3 september 2006 and Thursday 7 September 2006. The researcher evaluated and completed the data until 11 September 2006. The Classroom Action Research cycle The Classroom Action Research was carried out through two cycles to see the increase in vocabulary learning skills by using Jumbled Words media in grade I students at SD Negeri II Widang in taking English subjects. Each cycle is carried out following the planning procedures, actions, observation, and reflection. Research Subjects As the subject in this study were students of class I at SD Negeri II Widang Tuban in the academic year of 2006/2007 with a total of 33 students, consisting of 19 boys and 14 girls. The reason for choosing this class is done with the consideration that student learning outcomes still need to be improved. In addition, learning by using the media Jumbled Words has never been carried out at the school. C. Variables Investigated The variable that was targeted in the Classroom Action Research was the improvement of the vocabulary ability using the media of Jumbled Words towards English subjects in students class I at SD Negeri II Widang. In addition to these variables there are still several other variables, namely: 1). Variable Input: Students class I at SD Negeri II Widang. 2). Variable Process: Application of Jumbled Words media learning. 3). Variable Out put: Students' ability to learn about vocabulary. Action Plan This research was conducted by providing actions in the form of: Research Plan This research was conducted by giving actions using the media Jumbled Words, English subjects, the subject of vocabulary chapter 2 about the food and Beverage, in the hope of an increase in student achievement. In planning the research activities include: a). Preparatory implementation of The classroom action research. b). Participant preparation: 1). Give a simulation to the teacher about the implementation. 2). Consolidating with teachers about the procedures for conducting research and Job description: a). Development of research instruments and scenarios, b). Prepare teaching aids used in research c). Develop an action plan The action that will be given is in the form of the use of the media of Jumbled Words, and the areas of development that are expected to increase are Affective, cognitive and psychomotor aspects, among which aspects include processing learning outcomes. Research Implementation In accordance with the type of research chosen, namely classroom action research, this study uses a research model from Kemmis and Tagart, which is spiral shaped from one cycle to the next cycle. This research is carried out through two cycles, each cycle consisting of the following activities: Cycle I Planning In the planning phase of the first cycle begins with joint reflection and analysis between researchers and colleagues on student learning outcomes, identifying problems, analyzing problems and finding alternative solutions to problems. From the above results the researchers did things as follows: 1). Arrange lesson cycle I focused on planning corrective steps or action scenarios that are expected to improve student ability in learning. In this learning improvement plan the researchers used the media of Jumbled Words 2). Prepare teaching materials, student worksheet I and Jumbled Words media that will be used by students in the learning process 3). Prepare data collection instruments, namely: a). Observation sheet activities of students and teachers during the assignment, b). Final learning test sheet 4). Planning aspects observed and assessed from the implementation of learning improvement, namely preparation, material clarity, organizing, training and guidance, closing. 5). Plan success criteria for learning improvement. In this study learning success is determined if 85% of students achieve mastery learning with a minimum value of 75. Implementation In the implementation phase of the first cycle the researcher is assisted by the teacher (collaborator) implementing the learning scenario as planned in the RPP as follows: 1). Regards. 2). Prayers together. 3). Attendance 4). The teacher explores the initial knowledge of students about the material that will take place. 5). The teacher gives questions about the lesson that will take place. 6). Students sing a song called Tourims Places together. 7). Students form 4 groups. 8. Each group of students is given time to read the teaching material for the Exciting Place Chapter. 9). Students close the book and collect on the teacher's desk. 10). Students work on worksheet 1. 11.) Each group of students mentioned food and beverage using Jumbled Words. 12). The fastest and correct student is the winner. 13). The teacher concludes about material that has already taken place. 14). Students listen to the motivation of the teacher to study hard. 15). Prayers together. 16). Closing. Observation At this stage the researcher together with colleagues carries out the data collection process and learning outcomes, for further processing, analysis, and interpretation. The research instruments used were: 1). Final evaluation evaluation test This instrument is used to determine student learning outcomes as a benchmark for measuring student ability and student learning completeness in mastering the material. This instrument was made by researchers and then consulted with colleagues concerned. Evaluation tests are used to obtain data on student learning outcomes after the learning process. This test is done at the end of learning. 2). Observation sheet when learning This instrument is used to measure the ability of teachers to manage learning. And used to determine student activities in the learning process. Reflection The results obtained in the observation process are collected and analyzed. From this analysis, the research team did a self-reflection on whether the vocabulary ability by using Jumbled Words media can improve learning achievement in odd semester I students in SD Negeri II Widang. From these results the teacher designs actions for the second cycle. Table 3.1. Cycle Activities I No Planning Implementation Data collection Reflection 1 Planning teaching materials Worksheet I, Jumbled Words media Explain vocabulary material related to exciting Places, using Jumbled Words media Observing the teacher in carrying out learning by using jumbled Words media Noting the results of observations 2 Develop RPP observation sheets and evaluation sheets Assign students in groups to assemble Jumbled Words so that they become vocabulary Observe student behavior when working on exercises both in groups and individually Evaluate Observation results 3 Plan learning success criteria One group representative presented the results of his work Observing each student's mastery of the material Analyzing learning outcomes 4 - Distributing evaluation sheets - Share the shortcomings for the next cycle Cycle II Planning The planning phase of the second cycle begins with joint reflection and analysis between researchers and colleagues on student achievement, identifying problems, analyzing problems and looking for alternative solutions to problems. From the above results the researcher did the following things: 1). Prepare a Learning Improvement Plan for cycle II by taking into account the deficiencies that occur in the improvement of cycle I. 2). Prepare teaching materials, student worksheets II that will be used by students in the learning process 3). Prepare data collection instruments, namely: a). Observation sheet of student activities during the assignment. b). Final learning test sheet 4). Planning aspects observed and assessed from the implementation of learning improvement, namely preparation, material clarity, organizing, training and guidance, closing. Implementation In the implementation phase of the second cycle the researcher is assisted by the teacher (collaborator) implementing the learning scenario as planned in the RPP namely the Teacher implements learning about the vocabulary material by using Jumbled Words media based on the learning plan the results of reflection in cycle I. Observation At this stage the researcher and teacher observe Jumbled Words' media learning activities as in cycle I Reflection The research team reflected on the implementation of the second cycle as in cycle I, as well as analyzing to make conclusions on the implementation of learning using Jumbled Words media on student achievement in English subject vocabulary in SD Negeri II Widang. Table 3.2. Cycle Activities II No Planning Implementation Data collection Reflection 1 Plans to improve learning by integrating the results of reflection into I so that the second cycle is more effective Explain vocabulary material related to Exciting trip using jumbled Words media Observing the teacher in implementing learning by using jumbled letters media Noting the results of observations 2 Planning media teaching materials jumbled words and Worksheet II Assign students as a group to arrange jumbled words into a vocabulary Observe student behavior when working on exercises both in groups and independently Evaluate the results of observations 3 Arrange observation sheet observation sheet teacher and student observation sheet and evaluation sheet One group representative presented the results of his work Observing each student's mastery of the material Analyzing the results of observations 4 Plan criteria for the success of learning improvement Distributing evaluation sheets - Correcting deficiencies for the next cycle Data Data Sources Sources of data in this Classroom Action Research are: Student To get data about student understanding during the process of teaching and learning activities Teacher To see the level of successful implementation of Jumbled Words media and student achievement in the learning process Peers / collaborators According to Suharsini Arikunto, (2009), peers / collaborators are intended as a source of data to see the implementation of Class Room Action Research in a comprehensive way, both in terms of students and teachers. Data Collection Techniques Data collection techniques in this study were made as much as possible in order to get data that is truly valid, the researchers conducted data collection in the following ways: 1) Observation Is a process of direct observation or sensing of conditions, situations, processes, and behaviors while the learning process is taking place. Observation is used to collect data about student activities in the Teaching and Learning Process and the application of Jumbled Words media that are carried out by teachers and researchers. The things observed include: a). Teacher activities in the learning process by using the media Jumbled Words. b). Student activities during learning using Jumbled Words media. There are two observation sheets that are used namely, Affective and psychomotor observation sheets. This observation sheet is filled in when the KBM process is taking place. 2) Observation sheets (Affective and Psychomotor Assessment) in groups Observations on the activities of students in groups are carried out to provide affective assessments to students in groups. These observations are carried out when students learn in groups. In learning activities there are two things that are observed include affective and psychomotor assessments. Aspects observed to be given an affective assessment of student activities in small groups include: a). Activity in groups, b). Enthusiastic, c). Compactness, d). Discipline, e). Creativity. While the psychomotor assessment of students is, cohesiveness in discussing the material in each group. 3) Test of learning outcomes Retrieval of data by means of learning achievement tests that requires answers to student achievement when applied Jumbled Words media. In using tests, researchers use instruments in the form of a set of test questions. Written tests can be divided into two, namely: a). Pre test. Pre test is done before students do learning using the media Jumbled Words Pre test aims to find out students' understanding and initial knowledge about the material to be delivered. b). Post test. Post tests were given after students did learning using Jumbled Words media, aimed at knowing students' understanding and knowledge about the material that was delivered. In carrying out this written test the researcher uses an evaluation carried out at the end of the learning using the Post Test. 4) Documentation The document is a written report about an event whose contents consist of an explanation and thought of the event. Documents consist of books, letters, official documents, photographs. In this study the documentation method is used to collect data available at school institutions as supporting data. In this study the data obtained does not mean anything because the data is still raw data. For this reason, it is necessary to analyze data so that the results can be interpreted in accordance with the formulation of the problem. In this study the interpretation of the criterion reference score or test is used. Data Analysis Data analysis is a method used in processing data that is closely related to the formulation of the problem that has been proposed so that it can be used to draw conclusions. The data obtained will be processed and analyzed qualitatively, namely: Qualitative data. Suharsini Arikunto, (2009) argues that data in the form of information in the form of sentences that provide a picture of reality or facts in accordance with the data obtained with the aim of knowing the learning outcomes achieved by students as well as knowing students' responses to student activities and activities during the learning process takes place. To analyze the level of success or the percentage of students' mastery learning after the teaching and learning process takes place at each cycle, carried out by giving an evaluation in the form of written test questions at each end of the cycle. This analysis is calculated using simple statistics as follows: Task Assessment and Tests Researchers add up the value obtained by students then divided by the number of students in the class so that the average value is obtained. This average value is obtained using the formula: X = Σ X Σ N Keterangan : X= Average value Σ X = The sum of all student grades Σ N = Total students For mastery learning There are two categories of mastery learning, individually and classically. According to Sudjana, (1988), based on the instructions for implementing teaching and learning, researchers assume that the media of Jumbled Words is said to be successful in increasing student achievement in the ability to understand vocabulary lessons if students are able to do the type of vocabulary and fulfill learning achievement of 85% or with grades minimum of 70. To calculate the percentage of learning achievement used the following formula: P = f X 100% N P = Percentage to be searched for f = The sum of all answers obtained N = The number of observation items multiplied by the appropriate score The results of the research that have been obtained are classified into the form of scoring students' grades by using the criteria for the assessment standards of SD Negeri II Widang as follows: 90 – 100 : Very Good 70 – 89 : Good 50 – 69 : Good Enough 0 – 49 : Not good Performance Indicators Performance Indicator is a criterion used to see the level of success of Classroom Action Research activities in increasing or improving PBM in class. Suharsini Arikunto, (2009) believes that performance indicators must be realistic and measurable (clearly how to measure them). Looking at the background of the problem and to improve vocabulary skills, the following indicators are used: 1. Students a. Tests: Average test scores of students (pre-test and post-test). b. Observation: The activeness of students in the learning process 2. Teacher a Documentation: Student presence b. Observation: Observation results Research Team and Its Tasks This class action research uses a form of collaboration. In this case the collaborator (the teacher in question) is an English subject teacher namely Ms. Ani Rahmawati ’S.Pd. In addition to being a collaborator, the teacher also acts as an observatory together with researchers in the implementation of learning in the classroom. They are fully responsible for this class action research. Researchers and collaborators are fully involved in planning, acting, observing, and reflecting on each cycle. This class action research was carried out in two cycles that were considered capable of fulfilling the desired results and overcoming the existing problems. RESEARCH RESULTS AND DISCUSSION The results of this study are described in stages in the form of cycles of learning carried out in the teaching and learning process in class. In this study learning is carried out in two cycles, as described below: Cycle I Research Results Planning cycle I The implementation of the first cycle was carried out in class I of SD Negeri II Widang which consisted of 33 students on wednesday, september 4, 2006, the first and second study hours with an allocation of 2 hours (2 x 35 minutes). Cycle I is an English learning process with the subject of the food and beverage by using Jumbled Words media. At this stage the researcher prepares a learning kit consisting of RPP, LK to I, Jumbled Words media, Teacher and student observation sheets, research instruments, and supporting teaching tools. Implementation and Observation of cycle I The learning process in the first cycle is carried out in accordance with the learning plan that has been made. The learning activities carried out were initiated by the teacher by inviting students to sing the days song to dilute the student's learning atmosphere, so that before the students did the learning they did not have a tense feeling but remained happy. Students were very excited to sing the days song that the researchers deliberately gave because in the song there were vocabularies related to thier daily activites. The teacher conditions students to be ready to take part in teaching and learning activities, because when teaching and learning activities will take place there are still some students who are busy. Then, to measure students' abilities, the teacher conducts questions and answers about the food and beverage material. There were only a few students who dared to answer aloud, while others did not answer because they were shy, not brave and lacked confidence and some were playing paper and stories about soap operas with their peers. At the time of core learning, the teacher explains the material using Jumbled Words media. And give assignments to students to arrange related words about the food and beverage in groups. The teacher forms groups of students with different levels of vocabulary. From the number of class I students there were 33 students divided into 4 groups, each of which consisted of 4 students and 1 group consisted of 9 students consisting of men and women, who had diverse academic abilities. In addition, the teacher also provides instructions to be conducted by students in learning vocabulary using the media of Jumbled Words. These guidelines include what students will do in groups, that is, each student must discuss and work together in groups to solve the problems contained in the worksheet and for members of the group who are capable or smarter are expected to help members who are less able. After the work is finished, the group leader is asked to present the results of the group discussion. The teacher also informs of the test at the end of the meeting and the appreciation for the group and students who can complete their assignments properly and in accordance with the specified time. Each student representative took an envelope containing Jumbled Words that had been prepared by the teacher. After the teacher explains the work instructions, students are welcome to open the envelope and arrange the various letters contained therein. The teacher gives a mark on the letter in front of the word so students do not have difficulty in doing it. The discussion in the work of Jumbled Words went pretty well, but smart students still dominated the discussion. During the discussion the teacher goes around guiding students who are having difficulties. After the discussion was over, the group representative presented the results of the discussion. Of the five groups, the discussion results were presented by each group in turn. Students explain what vocabulary they produce from Jumbled Words media. The teacher asks the meaning of each word presented by students into Indonesian. Students can answer compactly and correctly, but there are some students who don't answer. Students work on evaluation sheets individually. The classroom is very quiet because students take work seriously. Students collect evaluation sheets on the teacher. Reflection cycle I The discussion results obtained from the first cycle are as follows. The successes and failures that occurred in cycle I are: Researchers' observations of the teacher's activities, in learning activities have reached the success criteria 69.44% are in the pretty good category. This means that the criteria for success in learning English in the first cycle have not yet been achieved. Researchers' observations of student activities in learning activities have reached 57.5% success criteria. Being in the good enough category. This means that the criteria for student success in learning in cycle I have not yet been achieved. There are some children who still have difficulty in compiling Jumbled Words. In the implementation of discussions (in groups) are still dominated by children who have high abilities, so the need for individual guidance for all students and especially for all students with low ability. From some observations during the study, the researcher and the English teacher concluded that the implementation of the actions during the first cycle had not been successful, for this reason it needed to be improved and repeated in the second cycle. Cycle II Research Results Planning cycle II The implementation of the first cycle was carried out in class I at SD Negeri II Widang which consisted of 33 students on saturday, september 9, 2006, the first and second school hours with an allocated time of 2 hours (2 x 35 minutes). Planning in cycle II is based on the planning contained in cycle I. In cycle II researchers further enhance learning activities than what has been done in cycle I. In this cycle the researchers planned that in the discussion of vocabulary about the food and beverage by using the media Jumbled Words, class I students at SD Negeri II Widang, it was not maximal. At this stage the researcher prepares a learning tool consisting of Jumbled Words, RPP, LK to II, evaluation sheets, teacher and student observation sheets, research instruments, and supporting teaching tools. Implementation and Observation of cycle II The core activity begins with exploring students' knowledge about the vocabulary that has been taught in cycle I. Explanation from the teacher about working on Jumbled Words media. Then proceed with the implementation of student discussion in groups in working on Jumbled Words media. The division of the group in cycle II is the same as the division of the group in cycle I. Which in cycle II the class is divided into 4 groups, where each group consists of 8 students and 1 group consists of 9 students consisting of men and women, who have diverse academic abilities. In addition, the teacher also provides instructions to be conducted by students in learning vocabulary using the media of Jumbled Words. The discussion went very well, this is because many students who were very enthusiastic in completing the media Jumbled Words teachers were also more intensive going around giving guidance to students or groups who actually had difficulty in completing their assignments. Presentation of the results of group discussions is carried out alternately from group one to group four. All groups are very enthusiastic. Student activities during the second cycle presentation also increased. This is shown by students who are able to work on Jumbled Words media and find vocabulary in it. All groups can complete the task and present the results of the discussion well. c. Reflection cycle II 1) The observations of researchers on the activities of teachers in maintaining and improving the atmosphere of learning by using the media Jumbled Words, have reached the criteria of success 86.1% are in the good category. This means that the criteria for the success of English teacher activities in learning in cycle II have been successful. 2) Student activities in working on Jumbled Words media are also very good which reach 90% success criteria. Students are able to find vocabulary from various types of letters that have been randomized in the media of Jumbled Words. 3) Researchers' observations of student activities in learning activities have reached 92.30% success criteria. Being in the category is very good. This means that the criteria for student success in learning in cycle II have been successful. 4) The observation shows that there are no more students who are still having difficulty in understanding the meaning and kinds of vocabulary around tourism places. In carrying out discussions (in groups) all children already have the same ability, so there is no need for individual guidance for all students. 5) From the results of the study, students using Jumbled Words media are more creative in arranging various letters into a vocabulary 6) Learning vocabulary by using Jumbled Words media turns out to have a positive impact on student learning activities. 7) Students are getting closer and dare to ask their group friends or teachers if there are things that are not yet understood. 8) Students are increasingly skilled at compiling vocabulary from several letters that have been randomized before. 9) From a number of observations during the study, the researcher and the English teacher concluded that the implementation of the actions during the second cycle had been successful, for that it was no longer necessary to repeat the actions of the third cycle. Research Data Observation Results Student Activity Table 4.1 Data on Observation of Student Activities During the Vocabulary Learning Process Using Media Jumbled Words. No Rating Indicator Cycle I Cycle II 1 2 3 4 1 2 3 4 1 Readiness of students to follow the learning process √ √ 2 Students orderly when class starts. √ √ 3 Students are ready with books or complete learning tools. √ √ 4 Listen and pay attention to the explanation of the teacher or fellow students (interaction in learning). √ √ 5 Students respond to what the teacher instructs. √ √ 6 Students can discuss well when in groups. √ √ 7 Students can explain the material well when in groups. √ √ 8 Students are enthusiastic in arranging words by using jumbled letters √ √ 9 Students actively ask questions. √ √ 10 Student questions have a high weight. √ √ Amount 22 36 Average 2,2 3,6 Percentage (%) 55 90 Informations: 4 = Very good 3 = Good 2 = Enough 1 = Less From the results of observations of Skilus I conducted by researchers on student learning activities the total score obtained was 22 and the maximum score was 40. Thus the results of the percentage score was 55%, which means that student activities during the learning activities were in the sufficient category From the results of observations of the second cycle conducted by researchers on student learning activities the total score obtained was 36 and the maximum score was 40. Thus the results of the percentage score was 90%, which means that student activities during learning activities were in the very good category. In the learning process takes place students are more actively listening to the teacher's explanation, doing the assignments using Jumbled Words media, and interacting with other friends. In the second cycle, student activities have increased where the assessment indicators are all done well and are in good and very good qualifications. 2. Teacher's Activity Table 4.2 Data on Observation of Teacher Activity During the Vocabulary Learning Process Using Media Jumbled Words No Rating Indicator Cycle I Cycle II 1 2 3 4 1 2 3 4 1 The teacher conveys the learning objectives. √ √ 2 A systematic and coherent explanation of material. √ √ 3 Overall teacher attention for all students. √ √ 4 The teacher explains how to use jumbled Words media √ √ 5 The suitability of the media with teaching materials, learning indicators and students' character. √ √ 6 The teacher forms students into groups with students' vocabulary skills diverse. √ √ 7 The teacher guides students who have difficulties. √ √ 8 The teacher uses simple and clear language that is easily understood by students. √ √ 9 Teacher's neat and impressive appearance. √ √ 10 The teacher conducts questions and answers with students √ √ 11 Equitable question distribution to students. √ √ 12 Teacher questions are clear, purposeful and do not confuse students. √ √ 13 The teacher provides appropriate reinforcement to students. √ √ 14 The teacher evaluates. √ √ 15 The teacher gives individual assignments. √ √ 16 The teacher checks the work of students. √ √ 17 The teacher concludes the material that has taken place. √ √ 18 The teacher provides psychological encouragement to students to continue to study diligently at the end of the meeting. √ √ Amount 49 62 Avarage 2,72 3,4 Percentage (%) 68 86,1 Informations : 4 = Very Good 3 = Good 2 = Enough 1 = Less The results of observations of teacher activities in teaching and learning activities in the first cycle are still relatively low with the acquisition of a score of 49 or 68%, while the ideal score is 72. This is not in line with expectations because the indicator of success is achieved when the teacher's activity reaches 85%. This happens because they stand more in front of the class and give less direction to students. The results of observations of teacher activities in teaching and learning activities in the second cycle have reached indicators of success with the acquisition of a score of 62 or 86.1%, while the ideal score is 72. This is in line with expectations because the indicator of success is achieved when the teacher's activity reaches 85%. This shows a significant increase in vocabulary learning using Jumbled Words media Learning Test Results The presentation stage of learning outcomes data on Animals subject vocabulary using Jumbled Words media after data collection is done according to the procedure, the next step is the presentation of research data in accordance with the tests conducted. Tabel 4.3 Evaluation Value of Cycle I and II Class I Students of SD Negeri II Widang. Vocabulary Learning Using Media Jumbled Words No Rating Indicator Cycle I Cycle II Pre Tes Post Tes PostTes 1 C.N 50 60 60 2 R.R 50 60 70 3 M.I 50 65 77 4 N.Z.A 50 60 84 5 S.A 55 60 70 6 A.Z 65 70 70 7 K.F 50 65 65 8 A.M 60 70 77 9 C.N.M 60